Personality Structure and Attachment in Bipolar Disorder - Wagner-Skacel, Jolana; Bengesser, Susanne; Dalkner, Nina; Mörkl, Sabrina; Painold, Annamaria; Hamm, Carlo; Pilz, René; Rieger, Alexandra; Kapfhammer, Hans-Peter; Hiebler-Ragger, Michaela; Jauk, Emanuel; Butler, Mary I.; et al. (Frontiers in Psychiatry, 2020)
Background: An impairment of self and interpersonal functioning has an impact on coping strategies, regulation of affect and stress. Little is known so far about the impairment of personality functioning in patients with bipolar disorder (BD). The aim of this study is to assess the effects of personality structure and attachment in BD patients on the symptom burden. Methods: Forty-six patients with the diagnosis of BD were assessed by the 12-item Operationalized Psychodynamic Diagnosis Structure Questionnaire (OPD-SQS), the short version of Experience in Close Relationship-revised (ECR-R-D) and the Brief Symptom Inventory-18 (BSI 18) to determine the level of personality functioning, attachment patterns and symptom load. Results: We observed positive correlations between personality difficulties, insecure attachment and symptom load in patients with BD. A low level of structural integration and an insecure attachment style in patients with BD were accompanied by a significantly higher symptom load (r = 0.66, p ≤ 0.01). Interestingly, there were no significant differences in the structural integration (T(1.44) = -0.93, p = 0.357) and in the attachment style (attachment related avoidance: (T(1,44) = 1.50, p = 0.140); attachment related anxiety (T(1,44) = -0.781, p = 0.439) of study participants with BD when compared to the normative value of the general population. Limitations: Our limitations are the small sample size of our group and the lack of a control group. Conclusion: In general, our results suggest that there is a link between personality structure and affective dynamics including depressive, anxiety and somatization symptoms in BD. These findings underline the increasing importance of assessing personality structure and attachment for diagnosis and treatment planning of BD.